Zoneamento agroecológico do município de Apodi/RN - Santana Júnior, Henrique Eufrásio de (2010)
The aim of the paper is to carry out a geo-environmental characterization of Apodi District, in Rio Grande do Norte State, as a support to agro-ecological zoning studies on that region. The first methodology action was to accomplish a comprehensive bibliography review on the subject, followed by observation of satellite images and their processing throughout geographic information systems (SIG), as well as technical visits to various places in order to verify in loco the preset conditions of the soil and the environmental degradation problems in those areas. The paper also presents data about the socio-economy and physic-natural local aspects of the land, required to the implementation of zoning studies which are one the most important tool to the planning and organization of the use of the soil containing a sustainable cattle-raising activity. As a result, thematic maps describing the physic-natural features and analysis of the socio-environment data, indispensable to the agro-ecological zoning, have been provided